An Update to the TraVA Database: Time Series of Capsella bursa-pastoris Shoot Apical Meristems during Transition to Flowering - Anna V. Klepikova; Artem S. Kasianov (Data, 2020)
Transition to flowering is a crucial part of plant life directly affecting the fitness of a plant. Time series of transcriptomes is a useful tool for the investigation of process dynamics and can be used for the identification of novel genes and gene networks involved in the process. We present a detailed time series of polyploid Capsella bursa-pastoris shoot apical meristems created with RNA-seq. The time series covers transition to flowering and can be used for thorough analysis of the process. To make the data easy to access, we uploaded them in our database Transcriptome Variation Analysis (TraVA), which provides a convenient depiction of the gene expression profiles, the differential expression analysis between the homeologs and quick data extraction.